Why are human animacy judgments continuous rather than categorical? A computational modeling approach - Westbury, Chris (Frontiers in Psychology, 2023)
The concept of animacy is often taken as a basic natural concept, in part because most cases seem unambiguous. Most entities either are or are not animate. However, human animacy judgments do not reflect this binary classification (Radanović, Westbury, and Milin, 2016). They suggest that there are borderline cases, such as virus, amoeba, fly, and imaginary beings (giant, dragon, god). Moreover, human roles (professor, mother, girlfriend) are consistently recognized as animate by far less than 100% of human judges. In this paper I use computational modeling to identify features associated with human animacy judgments. I approached the problem in two ways, modeling human animacy and living/non-living judgments using both bottom-up predictors (the principal components from a word embedding model) and top-down predictors (cosine distances from the names of animate categories). The results suggest that human animacy judgments may be relying on information obtained from imperfect estimates of category membership that are reflected in the word embedding models. Models using cosine distance from category names mirror human judgments in distinguishing strongly between humans (estimated lower animacy by the measure) and other animals (estimated higher animacy by the measure). These results are consistent with a family resemblance approach to the apparently categorical concept of animacy.